Development Guidelines for Administration of the School’s Support System in Digital Era of the Opportunity Expanded School Under the Office of Primary Educational Service Area in Buriram Province - Maneeputtaworasakul, Napassakorn; Kakkeaw, Vasanchai; Sittisuea, Thanyathap (Academic MCU Buriram Journal, 2023)
The objectives of this research were: 1) to study guidelines for the development the current administrative conditions of the student supporting system in digital era of opportunity expansion schools under the Primary Educational Service Are Offices in Buriram province; 2) to compare guidelines for the development the administration of the student supporting system in digital era of opportunity expansion schools classified by school size; and 3) to provide the administrative development guidelines for the student supporting system in digital era of opportunity expansion schools under the Primary Educational Service Are Offices in Buriram province, The sample group consisted of 318 school administrators and teachers who are responsible for the student supporting system, The statistics used for data analysis were: Frequency, percentage, average, standard deviation, F-test, and Scheffe’spair difference test, a content analysis was also applied for data analysis. The research result found that: 1. According to the current guidelines for the development, administrative conditions of the student supporting system in digital era of opportunity expansion schools under the Primary Educational Service Are Offices in Buriram province, the study showed that the overall current condition is at a high level. When considering each aspect, it was found that the average current condition is at a high level in all aspects. 2. Owing to the comparison guidelines for the development of the administration of the student supporting system in digital era of opportunity expansion schools classified by school size, the study showed that, in general, there are statistically significant differences at .05 level among schools with different size according to a pair comparison using Scheffe’s method. 3. The administrative development guidelines for the student supporting system in digital era of opportunity expansion schools. Finally, the study revealed that the suitability, feasibility, and profitability at the highest level in all aspects.